Symbole i wartości w wychowaniu chrześcijańskim = The symbols and values in Christian education - Loba, Piotr (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The contents and functions of selected symbols and values of Christian education have been presented in the dissertation.
Keywords: wartość - chrześcijaństwo; symbol - chrześcijaństwo; wychowanie